Controlled synthesis, formation mechanism, and great enhancement of red upconversion luminescence of NaYF4:Yb3+, Er3+ nanocrystals/submicroplates at low doping level - Zhao, Junwei; Sun, Yajuan; Kong, Xianggui; Tian, Lijin; Wang, Yu; Tu, Langping; Zhao, Jialong; Zhang, Hong (The journal of physical chemistry. B, 2008)
Strong red upconversion luminescence of rare-earth ions doped in nanocrystals is desirable for the biological/biomedical applications. In this paper, we describe the great enhancement of red upconversion emission (4F9/2 --> I15/2 transition of Er3+ ion) in NaYF4:Yb3+, Er3+ nanocrystals at low doping level, which is ascribed to the effectiveness of the multiphonon relaxation process due to the existence of citrate as a chelator and cross relaxation between Er3+ ions. The dissolution-recrystallization transformation, governing both the intrinsic crystalline phase (cubic and/or hexagonal phase) and the growth regime (thermodynamic vs kinetic), is responsible for the phase control of the NaYF4 crystals. The possible formation mechanism of the NaYF4 crystals and the role of trisodium citrate which acts as a chelating agent and shape modifier are discussed in detail. It is also found that the alpha --> beta phase transition is favored by the high molar ratio of fluoride to lanthanide and high hydrothermal temperature as well as long hydrothermal time.